Tuning the surface coating of IONs toward efficient sonochemical tethering and sustained liberation of topoisomerase II poisons - Michalkova, Hana; Strmiska, Vladislav; Kudr, Jiri; Skubalova, Zuzana; Tesarova, Barbora; Svec, Pavel; Richtera, Lukas; Zitka, Ondrej; Adam, Vojtech; Heger, Zbynek (International journal of nanomedicine, 2019)
Background: Iron oxide nanoparticles (IONs) have been increasingly utilized in a wide spectrum of biomedical applications. Surface coatings of IONs can bestow a number of exceptional properties, including enhanced stability of IONs, increased loading of drugs or their controlled release. Methods: Using two-step sonochemical protocol, IONs were surface-coated with polyoxyethylene stearate, polyvinylpyrrolidone or chitosan for a loading of two distinct topo II poisons (doxorubicin and ellipticine). The cytotoxic behavior was tested in vitro against breast cancer (MDA-MB-231) and healthy epithelial cells (HEK-293 and HBL-100). In addition, biocompatibility studies (hemotoxicity, protein corona formation, binding of third complement component) were performed. Results: Notably, despite surface-coated IONs exhibited only negligible cytotoxicity, upon tethering with topo II poisons, synergistic or additional enhancement of cytotoxicity was found in MDA-MB-231 cells. Pronounced anti-migratory activity, DNA fragmentation, decrease in expression of procaspase-3 and enhancement of p53 expression were further identified upon exposure to surface-coated IONs with tethered doxorubicin and ellipticine. Moreover, surface-coated IONs nanoformulations of topo II poisons exhibited exceptional stability in human plasma with no protein corona and complement 3 binding, and only a mild induction of hemolysis in human red blood cells. Conclusion: The results imply a high potential of an efficient ultrasound-mediated surface functionalization of IONs as delivery vehicles to improve therapeutic efficiency of topo II poisons.
Keywords: Cell Death; mužské pohlaví; Male; buněčné linie; DNA-topoisomerasy typu II; Humans; nanočástice; doxorubicin; uvolňování léčiv; DNA Topoisomerases, Type II; Topoisomerase II Inhibitors; lidé; hojení ran; Sonication; buněčná smrt; Cell Movement; biokompatibilní potahované materiály; Wound Healing; povrchové vlastnosti; Kinetics; Drug Liberation; Ferric Compounds; vibrace ultrazvukové; Static Electricity; kinetika; pohyb buněk; železité sloučeniny; Cell Line; Coated Materials, Biocompatible; inhibitory topoisomerasy II; Surface Properties; Nanoparticles; statická elektřina; Doxorubicin